Le paysage spatial dans la bande dessinée de science-fiction - Irène Langlet (ReS Futurae)
The spatial landscape is a so typical trope of SF that one can see it as a landscape of the genre itself. In this hypothesis, the landscape is not only a diegetic framework, but also an architextual framework. It refers less to referents (although imaginary) than to the iconic series of a genre, that of science fiction. However, the spatial landscape of SF is nourished by serious representations of astronomy, a major discipline of popular science. These two hypotheses are articulated here to show that the spatial landscape witnesses, in the bande dessinée, to the recognition of a visual genre culture but also to the knowledge of a science emblematic of modernity, and of its major technological adventure: the space race.By observing how the SF signature is constituted in a diversion from the astronomical rigor, I establish the architextual framework in which the aesthetic and formal question can be posited. Then I show how the so-called “9th art” has provided the expression of aesthetic emotion and science-fictional sublime. This emphasis on the emotions of science-fiction leads to argue, finally, that the bifurcation of the spatial landscape towards a “graphic culture” and a “sciencefictional culture” that do not overlap with the “astronomical culture” have in spite of all nourished scientific mediation at the turn of the 21st century.